Geoinformatic analysis of vegetation and climate change on intertidal sedimentary landforms in southeastern Australian estuaries from 1975–2015 - K. M. Al-Nasrawi, Ali; M. Hamylton, Sarah; G. Jones, Brian; A. Kadhim, Ameen (AIMS geosciences, 2018)
Vegetation canopies represent the main ecosystems on intertidal landforms and they clearly respond to changes in coastal environments. Climate change, including temperature, precipitation and sea level rise, are affecting the health and distribution of coastal vegetation, as well as the runoff and sedimentation rates that can impact coastal areas. This study has used the normalized difference vegetation index (NDVI) to investigate vegetation canopy dynamics on three different coastal sites in southeastern Australia over the past 47 years (1975–2015). NDVIs temporal-datasets have been built from satellite images derived from Landsat 1–8. These were then regressed to the climatic and geomorphic variables. Results show clear increases in NDVI at Towamba and Wandandian Estuaries, but a decline at Comerong Island (southeastern Australia). The sedimentation rate has the most significant positive impact on NDVI since it has the potential to provide additional space for vegetation. Temperature and sea level rise have positive effects, except on Comerong Island, but rainfall has no significant effect on the NDVI at any site. Different NDVI trends have been recorded at these three coastal sites reflecting different correlations between the vegetation, climatic and geomorphic (as independent) variables. The geomorphological characteristics of the highly-dynamic intertidal estuarine landforms, which are subject to active erosion and deposition processes, have the largest impact on vegetation cover and, hence, on NDVI. Assessing the vegetation canopy using NDVI as an evaluation tool has provided temporal-dynamic datasets that can be correlated to the main individual environmental controls. Such knowledge will allow resource managers to make more informed decisions for sustainable conservation plans following the evaluation the potential consequences of any environmental changes.